일부 건강관련 과목 교사의 학부전공만족 및 직업만족에 관한 조사연구 : 서울시내 여자고등학교를 중심으로 - 한승환 (연세대학교 보건대학원, 1989)
[한글] 건강관련 과목 철사의 직업만족과 학부전공만족을 조사하고 직업만족에 영향을 미치는 요인을 파악하고자 서울시내애 거주하는 일부여자고등학교 건강관련 과목 교사를 대상으로 1989년 4월 1일부터 4월 28일까지 설문조사를 실시하여 225부의 설문지를 회수하여 분석한 결과는 다음과 같다. 1. 조사대상자의 직업선택동기를 살펴보면 흥미와 적성 때문에 교직을 선택했다고 응답한 교사가 41.8%로 가장 많은 비율을 차지했고, 경제적 안정성 때문이 22.1%, 자기발전을 위한 시간적 여유 때문이 11.7%의 비율을 차지했다. 2. 일반적 특성에 따른 직업만족도를 살펴보면 담당과목, 근무기간, 학교유형, 직업선택동기 등에 따라 직업만족도는 통계적으로 유의한 차이를 보였다. 직업선택 동기별로 살펴보면 흥미와 적성 때문에 교직을 선택한 경우 다른 선택동기보다 직업만족도가 높게 나타났고 (P<0.01, t=2.59, df=180), 학교유형별로 살펴보면 사립학교에 재직중인 교사가 공립학교에 재직중인 교사보다 직업만족도가 높았다(P<0.05, t=2.10, df=51). 3. 일반적 특성에 따른 학부전공만족도를 살펴보면 담당과목, 성별전공선택동기 등에 따라 전공만족도는 통계적으로 유의한 차이를 보였다. 성별로 볼 때 남자가 여자보다 전공만족도가 높았으며(P<0.05,t=2.54, df=95), 학부전공 선택동기별로 보면 홍미와 적성때문에 전공을 선택한 경우 다른 선택동기보다 전공만족도가 높게 나타났다(P<0.01, t=4.21, df=211). 4. 직업만족도와 학부전공만족도의 상관관계를 살펴보면 학부전공만족도와 직업만족도는 긍정적인 상관관계가 있는 것으로 나타났으며 통계적으로 유의하게 나타났다(r=0.4310, p<0.01). 5. 직업만족도에 영향을 주는 요인을 살펴보면 조사대상자의 성별연령, 결혼여부, 근무기간, 학부전공, 학교유형, 직업선택동기, 학부전공만족도 등 8개의 독립변수 중에서 학부전공만족도가 가장 영향을 주는 요인이였으며 이 요인으로 18.6%정도 설명할 수 있었다 (R**2:0.1857, P<0.01). 6. 건강관련 과목 교사들의 현직업에 대한 불만사항은 조사대상자의 24.2%가 보수에 대한 불만을, 15.9%가 담당과목이 적성에 맞지 않아서 불만이라고 각각 응답했다. 7. 전직희망여부를 살펴보면 제반여건이 허락한다면 전직을 원한다고 응답한 교사가 55.9%로 과반수를 넘었으며, 전직희망직종을 살펴보면 전체 응답자의 51.3%가 교수를 원하는 것으로 나타났다. 이상을 살펴볼 때 건강관련 과목 교사들의 직업만족과 학부 전공만족은 긍정적인 상관관계가 있으며 직업만족에 가장 큰 영향을 미치는 요인도 학부전공만족이었다. 그러므로 직업만족도를 높이기 위해서는 교사들의 학부 전공만족도를 높여야 하며 학부전공선택시와 직업선택시 흥미와 적성을 보다 고려하여야 하며 교사들의 경제적 처우개선과 업무의 간소화로 불만사항을 해소하여야 할 것으로 사료된다. 그리고 건강관련 과목 교사들이 건강교육을 실시하는데 따른 애로사항과 개선할 사항이 무엇인가에 대한 연구와 함께 직업만족도와 학부전공만족도에 영향을 미치는 다른 요인들에 대한 계속적인 연구가 필요로 되어진다. A Correlational Study of the Satisfaction with the Subjects Majored in and The Job Satisfaction of Teachers teaching Course Content Related to Health Care. -Based on Teachers in Girls' High Schools in Seoul- Seung Han Man Graduate School of Health Science and Management Yonsei University (Directed by Professor Myung Ho Kim, M.D.) In an attempt to determine factors influencing satisfaction with job and subjects majored in a survey of teachers teaching courses that included health care content in girls' high schools in seoul was carried out. Data was obtained from 225 teachers by means of a questionnaire which was distributed from April 1 to April 28, 1989. 1. In regard to motivation of job selection, it was revealed that the greatest number (41.8%) of teachers who responded choose the teaching profession because of individual interest anti vocational aptitude, while 22.1% selected it because of economic stability and 11.7% selected it because of leisure time for self- improvement. 2. With regard to the relationship of job satisfaction to the general characteristics, the factors that were found to be statistically significant were years of teaching, school types and motivation in select of their job. Ta take another look at motivation in selection of job, it was found that the degree of job satisfaction was higher when the teaching profession was chosen because of the individual's interest and vocational aptitude rather than other motives(t=2.59, df=180, p<0.01). In regard to type of school, the degree of job satisfaction was higher for teachers of private schools than teachers of public schools(t=2.10, df=51, P<0.01). 3. With regard to the relationship of the subject's degree of satisfaction with the subject they majored in and general characteristics it was found that the factors that were found to be statistically significant were the subject they majored in, their sex and their motivation for selection of their major subject. When observed by sex, the subjects degree of satisfaction with their major subject was higher in the case of males than in the case of females(t=-2.54, df=96, P<0.05). While in regard to their motivation for selecting their major subject at college, it was found that the subject's degree of satisfaction with their college education was higher when the person selected their major subject in consideration of their interest and aptitude rather than other motives(t=4.21, df=211, P<0.01). 4. The correlation between the degree of job satisfaction and the degree of satisfaction with the major subject was found to be affirmatively correlated with each other, and the relationship was statistically significant(r=0.4310, p<0.01). 5. As to the factor influencing the degree of the job satisfaction among the general characteristics and the subject majored in, it was found that the degree of satisfaction with the subject majored in was the most influential factor, with 18.6% being explained by this factor(R**2=0.1857. p<0.01). 6. Of the respondents who were dissatisfied with their current job as teachers of health subject 24.2% were dissatisfied with their remuneration, while 20.4% were dissatisfied with their heavy schedule of teaching and other duties, and 15.9% were dissatisfied because of their unsuitable aptitude for the subject they are teaching. 7. In regard to whether or not they would wished to change their jobs, it was revealed that the majority of teachers preferred to change their jobs 55.9%, concerning the change in jabs they wished to make 51.3% of the respondents preferred to become professors. Based on the above findings, a conclusion that can be drawn is that a positive correlation exists between the degree of job satisfaction and the degree of satisfaction with their subject of major. It was also found that the factors influencing the job satisfaction the greatest were the satisfaction with the subject majored in. Therefore, in order to increase the degree of job satisfaction for the teachers it is essential for the person to be satisfied with their subject of major and the selection of an appropriate job taking into consideration their interest and aptitude of the individual. Thus, it is important to decrease dissatisfaction by improvement of the financial treatment of the teachers and the simplification of assigned job. Futher study is needed to determine the critical areas of difficulties and the means of improvement of teaching environment needed to improve job satisfaction subsequent to the implementation of health education by teachers, and at the same time, continuous endeavor should be made to solve other factor influencing the degree of job satisfaction and the subject's degree of satisfaction with college education. [영문] In an attempt to determine factors influencing satisfaction with job and subjects majored in a survey of teachers teaching courses that included health care content in girls' high schools in seoul was carried out. Data was obtained from 225 teachers by means of a questionnaire which was distributed from April 1 to April 28, 1989. 1. In regard to motivation of job selection, it was revealed that the greatest number (41.8%) of teachers who responded choose the teaching profession because of individual interest anti vocational aptitude, while 22.1% selected it because of economic stability and 11.7% selected it because of leisure time for self- improvement. 2. With regard to the relationship of job satisfaction to the general characteristics, the factors that were found to be statistically significant were years of teaching, school types and motivation in select of their job. Ta take another look at motivation in selection of job, it was found that the degree of job satisfaction was higher when the teaching profession was chosen because of the individual's interest and vocational aptitude rather than other motives(t=2.59, df=180, p<0.01). In regard to type of school, the degree of job satisfaction was higher for teachers of private schools than teachers of public schools(t=2.10, df=51, P<0.01). 3. With regard to the relationship of the subject's degree of satisfaction with the subject they majored in and general characteristics it was found that the factors that were found to be statistically significant were the subject they majored in, their sex and their motivation for selection of their major subject. When observed by sex, the subjects degree of satisfaction with their major subject was higher in the case of males than in the case of females(t=-2.54, df=96, P<0.05). While in regard to their motivation for selecting their major subject at college, it was found that the subject's degree of satisfaction with their college education was higher when the person selected their major subject in consideration of their interest and aptitude rather than other motives(t=4.21, df=211, P<0.01). 4. The correlation between the degree of job satisfaction and the degree of satisfaction with the major subject was found to be affirmatively correlated with each other, and the relationship was statistically significant(r=0.4310, p<0.01). 5. As to the factor influencing the degree of the job satisfaction among the general characteristics and the subject majored in, it was found that the degree of satisfaction with the subject majored in was the most influential factor, with 18.6% being explained by this factor(R**2=0.1857. p<0.01). 6. Of the respondents who were dissatisfied with their current job as teachers of health subject 24.2% were dissatisfied with their remuneration, while 20.4% were dissatisfied with their heavy schedule of teaching and other duties, and 15.9% were dissatisfied because of their unsuitable aptitude for the subject they are teaching. 7. In regard to whether or not they would wished to change their jobs, it was revealed that the majority of teachers preferred to change their jobs 55.9%, concerning the change in jabs they wished to make 51.3% of the respondents preferred to become professors. Based on the above findings, a conclusion that can be drawn is that a positive correlation exists between the degree of job satisfaction and the degree of satisfaction with their subject of major. It was also found that the factors influencing the job satisfaction the greatest were the satisfaction with the subject majored in. Therefore, in order to increase the degree of job satisfaction for the teachers it is essential for the person to be satisfied with their subject of major and the selection of an appropriate job taking into consideration their interest and aptitude of the individual. Thus, it is important to decrease dissatisfaction by improvement of the financial treatment of the teachers and the simplification of assigned job. Futher study is needed to determine the critical areas of difficulties and the means of improvement of teaching environment needed to improve job satisfaction subsequent to the implementation of health education by teachers, and at the same time, continuous endeavor should be made to solve other factor influencing the degree of job satisfaction and the subject's degree of satisfaction with college education.
보건학과/석사